The influence of a career education programme and individual psychometric assessment on the career maturity and career decidedness of standard ten pupils : a comparative analysis - Henen, Shirley (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1990.